Kinerja Aparat Pemerintah Desa Dalam Mewujudkan Otonomi Desa (Studi pada Desa Sidomulyo Kecamatan Kebonagung Kabupaten Pacitan) - Candra, Jovan Pramaditya (Jurnal Administrasi Publik, 2013)
Abstract: The Performance of Village Government in Realizing Village Autonomy. (Studies on Sidomulyo Village, Kebonagung Sub-District, Pacitan Regency). In the implementation of regional autonomy, local progress is very dependent on the performance of the local governments themselves to be able to to prove his ability in the process of the interaction of government and in mobilizing public participation. The purpose of this research is to describe and analyze the performance of Sidomulyo government, and for looking for the restricting and supporting factors in to realizing the village autonomy. The methods used in this researh is a qualitative method with descriptive approach, while the primary data collection through interviews and secondary data through library. The research results showed that the performance of village government in realizing village autonomy is still need to be improved, not only their performance to organized village government, but also their role to mobilizing public participation too. Keywords: performance, village government, village autonomy Abstrak: Kinerja Aparat Pemerintah Desa Dalam Mewujudkan Otonomi Desa (Studi pada Desa Sidomulyo Kecamatan Kebonagung Kabupaten Pacitan). Dalam pelaksanaan otonomi daerah sekarang ini, kemajuan daerah sangat bergantung pada kinerja pemerintah daerah itu sendiri untuk dapat membuktikan kemampuannya dalam proses interaksi pemerintahan dan dalam menggalang partisipasi publik. Tujuan dari penelitian ini adalah untuk mendeskripsikan dan menganalisa kinerja aparat pemerintah desa Sidomulyo, serta mencari faktor penghambat dan pendukung dalam mewujudkan otonomi desa. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan deskriptif, sementara pengumpulan data primer melalui wawancara dan data sekunder melalui studi pustaka. Hasil penelitian menunjukkan bahwa kinerja aparat dalam mewujudkan otonomi desa masih perlu diperbaiki, bukan hanya pada kinerja dalam penyelenggaraan pemerintah desa, akan tetapi juga peranannya dalam menggalang partisipasi publik. Â  Kata kunci: kinerja aparat, pemerintah desa, otonomi desa